Front Cover: Influence of Lithium and Lanthanum Treatment on TiO2 Nanofibers and Their Application in n‐i‐p Solar Cells (ChemElectroChem 14/2019). Issue 14 (24th June 2019) - Ambroz, Filip; Sathasivam, Sanjayan; Lee, Roxanna; Gadipelli, Srinivas; Lin, Chieh‐Ting; Xu, Shengda; Poduval, Radhika K.; Mclachlan, Martyn A.; Papakonstantinou, Ioannis; Parkin, Ivan P.; Macdonald, Thomas J.
Abstract : The Front Cover shows a scanning electron microscopy image of lanthanum‐treated TiO2 nanofibers rendered to show a three‐dimensional representation of the nanostructured solar cell. This work shows that the addition of lithium and lanthanum cations causes minimal substitutional or interstitial doping of TiO2 nanofibers. More information can be found in the Article by F. Ambroz et al. on page 3590 in Issue 14, 2019 (DOI: 10.1002/celc.201900532 ).